2013
DOI: 10.3109/14767058.2013.846316
|View full text |Cite
|
Sign up to set email alerts
|

Unsynchronized nasal intermittent positive pressure versus nasal continuous positive airway pressure in preterm infants after extubation

Abstract: NIPPV (although non-synchronized and delivered by single nasal prong) had a better effect than NCPAP after extubation of preterm infants on mechanical ventilation in respect to reducing the prevalence of post-extubation atelectasis, re-intubation and also death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 20 publications
1
20
3
2
Order By: Relevance
“…This study showed no evidence of gastrointestinal effects, nasal injury, pneumothorax, PDA, and ROP, as also demonstrated in other studies. [22][23][24][25] The NCPAP groups showed no occurrence of PIVH, whereas we found PIVH ! grade 3 and 4 in three infants in the NIPPV group, which was not significant (p ¼ 0.105).…”
Section: Discussioncontrasting
confidence: 47%
“…This study showed no evidence of gastrointestinal effects, nasal injury, pneumothorax, PDA, and ROP, as also demonstrated in other studies. [22][23][24][25] The NCPAP groups showed no occurrence of PIVH, whereas we found PIVH ! grade 3 and 4 in three infants in the NIPPV group, which was not significant (p ¼ 0.105).…”
Section: Discussioncontrasting
confidence: 47%
“…6 Kahramaner et al also concluded that nIPPV has a better effect than nCPAP after extubation of premature infants, as it reduced the occurrence of atelectasis, the need for re-intubation and even the number of deaths. 21 conclusion Although the distribution of the failure frequencies showed a numerically lower failure rate in premature infants treated with nIPPV compared to those undergoing nCPAP, there was no statistically significant difference between the two methods of ventilatory support after extubation.…”
Section: Discussionmentioning
confidence: 69%
“…10 In some studies we verified variable rates in relation to extubation failure, sometimes associated with lower birth weight and gestational age. 1, 15,20,21 As such, we sought to verify if there was a relationship between extubation failure in the two methods and the BW and GA, classification of the premature infant, and the MV time. We found that there was no significant difference between the association of the characteristics described and the methods under study.…”
Section: Discussionmentioning
confidence: 99%
“…43 A similar study showed a higher prevalence of re-intubation, post-extubation atelectasis, and mortality with premature infants supported with CPAP than with non-synchronized NIV. 44 In a retrospective study that compared synchronized NIV with non-synchronized NIV in a cohort of 200 premature infants, after adjusting for disease severity, there were no differences in the combined outcome of bronchopulmonary dysplasia and death. 45 Based on these findings with non-synchronized NIV, synchrony may not be important for predicting patient outcomes with NIV in premature infants.…”
Section: See the Original Study On Page 1478mentioning
confidence: 92%